Digital platform/mobile App to boost cycling for the promotion of sustainable mobility in mid-sized starter cycling cities - Meireles, Mário (2020)
According to the United Nations, cities will represent two-thirds of the world’s population in 2050, which presents some challenges, especially to the transportation sector. To improve the population’s quality of life and the sustainability of cities, mobility must be sustainable, and cycling will play an important role in achieving this. Literature shows that we can promote cycling with better infrastructures, through multimodality, and through behavioral changes. Promoting the use of bicycles through behavior can involve a number of aspects, but in this work, we explore what a digital platform should have in order to promote and increase bicycle usage, as well as to improve cycling conditions in a city. To evaluate what is needed, we conducted an analysis on different types of digital platforms that are available on the market in order to assess the main characteristics and outputs that they provide to cyclists, as well as the type of information that can and should be added to promote the use of bicycles in cities. Moreover, we also carried out a survey in a Portuguese mid-sized “starter cycling city”, which showed, among other data, the relevance and type of information that a digital platform dedicated to cyclists should have in such types of cities.